Skin detection using color component subtraction and texture information / Rizal Mat Jusoh, Saiful Fadzli Salian and Sharifah Saliha Syed Bahrom - Mat Jusoh, Rizal; Salian, Saiful Fadzli; Syed Bahrom, Sharifah Saliha (Universiti Teknologi MARA Pulau Pinang, 2011)
This paper presents skin detection algorithm for detecting human skin regions in color images. The input color image in RGB format is converted into HSV format for color components subtraction.